2002
DOI: 10.1111/j.2042-3306.2002.tb05469.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced pulmonary perfusion redistribution in heaves

Abstract: SummaryThis study aimed to compare exercise-induced pulmonary perfusion redistribution in healthy vs. 'heavey' horses using scintigraphy, a minimally invasive technique. Six healthy (A) and 5 'heavey' horses in remission (B I ) and during clinical signs of disease (B II ) were investigated. Dimensions of the exercising pulmonary perfusion (Q E ) images were expressed in percent of the resting perfusion (Q R ) images. Computed Q E to Q R ratios (Q E /Q R ) images enabled the definition of the region more perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…They showed that the caudodorsal region of the thorax experienced larger pressure oscillations than other regions, and post mortem and histopathological studies have demonstrated that EIPH occurs precisely in that region . Ventilation heterogeneity is also accompanied by regional variations in perfusion . During exercise, blood flow increases primarily in the dorsal‐caudal region of the lung .…”
Section: Lower Airway Disorders and Their Effects On Respiratory Funcmentioning
confidence: 99%
“…They showed that the caudodorsal region of the thorax experienced larger pressure oscillations than other regions, and post mortem and histopathological studies have demonstrated that EIPH occurs precisely in that region . Ventilation heterogeneity is also accompanied by regional variations in perfusion . During exercise, blood flow increases primarily in the dorsal‐caudal region of the lung .…”
Section: Lower Airway Disorders and Their Effects On Respiratory Funcmentioning
confidence: 99%
“…; Harmegnies et al. ). However, there is evidence that this does indeed occur as blood flow was shunted to the nondependent lung in anaesthetized laterally‐recumbent horses (Stolk ).…”
Section: Discussionmentioning
confidence: 97%
“…This is also most likely the mechanism in the horse, although this is still unproven and somewhat in question since success of this therapy would require overcoming gravitational effects caused by the large vertical lung gradient in an adult horse. Although normal pulmonary blood flow distribution in the horse is only partially gravity-dependent, the fact that the shunt occurs in the dependent lung means that blood redistributed from the shunt would have to more against gravity (Dobson et al 1985;Bernard et al 1996;Hlastala et al 1996;Erickson et al 1999;Harmegnies et al 2002). However, there is evidence that this does indeed occur as blood flow was shunted to the nondependent lung in anaesthetized laterally-recumbent horses (Stolk 1982).…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that perfusion heterogeneity is greater in horses suffering from recurrent airway obstruction than in healthy horses. 44 Vascular diameter is modulated by smooth muscles that respond to vasoactive compounds. A wide range of mediators can modulate vascular smooth muscle tone, and among these epinephrine, norepinephrine, dopamine, prostaglandin and endothelin, 45 which is notably potent, are vasoconstrictors, and isoproterenol, bradykinin, histamine, nitric oxide and acetylcholine produce vasodilatation.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 99%